The association between serum selenium levels and pathological features of papillary thyroid cancer in 284 patients - Ge, Shenghui; Zhao, Junyu; Yao, Jinming; Fu, Hang; Tian, Yutian; Shan, Yuanyuan; Sun, Mengli; Feng, Jing; Dong, Jianjun; Liao, Lin (Frontiers in Endocrinology, 2023)
Objective: The relationship between serum selenium levels and papillary thyroid cancer (PTC), especially the pathological features, still remains controversial. We conducted this study to investigate the relationship between serum selenium levels and PTC in a Chinese population. Methods: Cross-sectional data of 284 patients with PTC were collected from the First Affiliated Hospital of Shandong First Medical University. The general clinical characteristics, serum selenium levels, and tumor pathological features were described in PTC. The association between serum selenium levels and pathological features in PTC was analyzed using SPSS 26.0 statistical software. Results: Our results showed that the median serum selenium level was 79.15 μg/L (IQR: 71.00 - 86.98 μg/L) in PTC patients. Serum selenium levels were lower in females than males (p = 0.035). Serum selenium levels were negatively correlated with the number of lymph node metastases (p = 0.048). High serum selenium (OR = 0.397, 95%CI: 0.217 - 0.725) and diastolic blood pressure (OR = 1.028, 95%CI: 1.005 - 1.051) were related factors for the incidence of bilateral tumors. High serum selenium (OR = 0.320, 95%CI: 0.166 - 0.617) and diastolic blood pressure (OR = 1.066, 95%CI: 1.031 - 1.103) were related factors for tumor multifocal incidence. Conclusions: The serum selenium levels of PTC patients in females were lower than males. High serum selenium levels might be a protective factor in PTC patients. Further research is necessary to better understand the influence of selenium on PTC progression.